Implikasi Hukum Ketidakterpenuhan Syarat Subjektif dalam Pasal 1320 Kitab Undang-Undang Hukum Perdata terhadap Keabsahan Perjanjian - Susi Sopiani; Vika Nur Senda; Mochamad Fajar Muzzamil (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
According to article 1 paragraph 3 of the 1945 Constitution of the Republic of Indonesia, it is stated that Indonesia is a legal state. In social life, agreements play a very important role as a legal instrument that regulates relationships between individuals and between institutions. According to article 1313 of the Civil Code which reads,